A method of pre-design feasibility study for an industrial estate development in Thailand - Wikhanes Wongwanishwatana; Ogunlana, Stephen O.; Jearkjirm, Vithool; Prapon Phasukyud; King's Scholarship I The Royal Thai Government (Bangkok : Asian Institute of Technology, 1993)
As a PRE-DESIGN consideration to guide owners in establishment of industrial estates and the overall factors involved are listed and considered as much as possible. In the first part, site feasibility study is considered. The consideration of the related factors are considered through interviewing some industrial estates establishments in Thailand. Good study and consideration of the possibility of the land to be developed is needed. An evaluating table of the factors which will guide owners on the possibility developing a piece of land as an industrial estate was drawn. Financial feasibility study was also conducted. Since industrial estate concerns the development of a tract of land by providing the infrastructure to serve the operating activities of industries inside, cost of development is the cost of infrastructure development. The infrastructure needed such as road, water work, etc. are considered. Data and information were given by the Design and Construction Department of the Industrial Estate Authority of Thailand (IEA T), and some industrial estates currently operating. The design criteria and guideline are summarized to get the pre-design estimation for adequate infrastructure facilities. The cost estimation is summarized from the rough average figure of development cost of some operating estates. Owners or new developers may derive a rough estimate of development cost before the design stage using the approach used in this thesis. Last part concerns operational feasibility study. The organization in form of functions and management are considered. Most of the estates use the hierarchy organization which is separated to departments according functional responsibilities and related function. The work programme with development process, teams, and construction and the supporting information about industrial estate establishment are included to inform sould-be new developers.
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1993
Keywords: Industrial districts -- Thailand